2011
DOI: 10.1016/j.jvs.2011.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation, fibrinolysis, and platelet activation in patients undergoing open and endovascular repair of abdominal aortic aneurysm

Abstract: The resultant prothrombotic diathesis after open surgical repair and EVAR may account for the high level of perioperative thrombotic complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
55
1
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 86 publications
3
55
1
6
Order By: Relevance
“…27,28 The present study confirms that patients with asymptomatic AAA exhibit a prothrombotic diathesis characterized by excessive thrombin generation as shown by markedly elevated PF1 ϩ 2 and TAT prior to EVAR. 4,15,17,[19][20][21][22] However, unlike some previous studies, no correlation was found between TAT, PF1 ϩ 2, and aneurysm diameter in this cohort.…”
Section: Discussioncontrasting
confidence: 96%
See 3 more Smart Citations
“…27,28 The present study confirms that patients with asymptomatic AAA exhibit a prothrombotic diathesis characterized by excessive thrombin generation as shown by markedly elevated PF1 ϩ 2 and TAT prior to EVAR. 4,15,17,[19][20][21][22] However, unlike some previous studies, no correlation was found between TAT, PF1 ϩ 2, and aneurysm diameter in this cohort.…”
Section: Discussioncontrasting
confidence: 96%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] A recent work from this group has shown that patients with AAA exhibit increased thrombin generation and activity as well as increased fibrin turnover. 15 Although these derangements appear to be correlated with aneurysm size, 14 increased fibrin turnover is also found in patients with small AAA. 1 This may show that hemostatic derangement is related to the size of intrasac thrombus than aneurysm size.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…AAA patients experience intensified plasma fibrinolysis and increased concentration of prothrombotic factors. Their blood exhibits elevated levels of D-dimers (fibrin fragments), PAI-1 (plasminogen activator inhibitor type-1),thrombin-antithrombin complexes, F1þ2 (prothrombin fragments) [7,9,10]. Haemostatic abnormalities are further aggravated by inflammatory processes associated with the aneurysm.…”
Section: Introductionmentioning
confidence: 99%